A Comparison of Explanation Methods of Encapsulation Efficacy of Hydroquinone in a Liposomal System - Khoshneviszadeh, Rabea; Fazly Bazzaz, Bibi Sedigheh; Housaindokht, Mohammad Reza; Ebrahim-Habibi, Azadeh; Rajabi, Omid (Archives of Advances in Biosciences, 2016)
One of the most important parameters describing the liposomal formulation of hydroquinone is encapsulation efficacy. For the efficacy evaluation of hydroquinone trapped in liposomal structure, there is a need to first separate liposome from the matrix surrounding it. There are various separation techniques; however, in this study, the three techniques of centrifuges with and without washing and dialysis were used. From among the laboratory techniques, an appropriate method is the one that offers responses with a high repeatability. The statistical calculations revealed that encapsulation efficacy with a direct method resulted from a separation via the techniques of dialysis and centrifuge without washing had the highest dispersion with SDs of 6.1 and 8.7, respectively, while the SD value in the technique of centrifuge with washing was 5.2. Through an indirect method, hydroquinone encapsulation efficacy showed the best repeatability with SD values of 2.8 and 2.1 by using the two techniques of centrifuge and centrifuge filtration, respectively. It seems that the treatments leading to the dilution of hydroquinone formulation would result in hydroquinone leakage and a reduction of encapsulation efficacy. It seems that measurement of hydroquinone encapsulation efficacy with an indirect method is a better choice; therefore, a centrifuge technique was utilized to report the mentioned efficacy at a speed of 45000 rcf and duration of 30 min due to having a reasonable price and ease of access.